Performance of the 1 h oral glucose tolerance test in predicting type 2 diabetes and association with impaired β-cell function in Asians: a national prospective cohort studyResearch in context - Michelle H. Lee; Eveline Febriana; Maybritte Lim; Sonia Baig; Liang Shen; Mayank Dalakoti; Nicholas Chew; Tze Ping Loh; Mark Chan; Kee Seng Chia; Alice Pik-Shan Kong; Alex R. Cook; et al. (The Lancet Regional Health. Western Pacific)
Summary: Background: Postprandial glucose concentration 1-h (1 h-PG) after an oral glucose tolerance test (OGTT) has similar or superior performance to 2 h-PG in predicting type-2 diabetes mellitus (T2DM) in several populations, and is simpler to obtain in clinical practice. However, studies in Asians are scarce. We investigated the utility of elevated baseline 1 h-PG in predicting T2DM incidence within three years, and its relationship with β-cell function in 1250 non-diabetic Asian participants. Methods: Participants underwent an OGTT, an intravenous glucose challenge and a hyperinsulinemic-euglycemic clamp to determine glucose tolerance, acute insulin response (AIR) and insulin sensitivity at baseline. OGTTs were repeated every six months until study completion to monitor T2DM conversion. Findings: The area under the receiver operating characteristic curve of 1 h-PG was not significantly different from 2 h-PG (AUC1h-PG = 0.883 vs. AUC2h-PG = 0.907; ΔAUC = −0.024, P = 0.124) and the optimal 1 h-PG cut-off was ≥10.7 mmol/L. When groups of high/low 1 h-PG and 2 h-PG at baseline were compared, AIR and disposition index were significantly lower in groups with high 1 h-PG, and both had a stronger correlation with 1 h-PG, indicating that impaired β-cell function was more strongly associated with elevated 1 h-PG than 2 h-PG. Interpretation: The ability of 1 h-PG to detect Asians at risk of developing T2DM within three years is on par with 2 h-PG and the optimal cut-off is 10.7 mmol/L. Elevated 1 h-PG is associated with β-cell dysfunction. We conclude that 1 h-PG can be considered as a primary OGTT time point to identify Asians at risk for T2DM, allowing for screening at a reduced time and cost, and with lower patient burden. Funding: National Medical Research Council (NMRC), Ministry of Health (MOH; Singapore) Industry Alignment Fund [NMRC/MOHIAFCat1/0048/2016] and Janssen Pharmaceuticals Inc. (USA).